Structure, ultrastructure and cation accumulation in quinoa epidermal bladder cell complex under high saline stress - Palacios, María Belén (2024)
Quinoa is a facultative halophyte with excellent tolerance to salinity. In this study, the epidermal bladder cell complex (EBCc) of quinoa leaves was studied to determine their cellular characteristics and involvement in salt tolerance. We used light microscopy, confocal RAMAN microscopy, confocal fuorescence microscopy, transmission electron microscopy, and environmental scanning electron microscopy complemented by energy dispersive X-ray analysis. Ionic content was quantifed with fame atomic absorption spectroscopy and with fame emission photometry. Results show that: (i) the number of EBCcs remains constant but their density and area vary with leaf age; (ii) stalk cells store lipids and exhibit thick walls, bladder cells present carotenes in small vesicles, oxalate crystals in vacuoles and lignin in their walls and both stalk and bladder cells have cuticles that difer in wax and cutin content; (iii) chloroplasts containing starch can be found on both stalk and bladder cells, and the latter also presents grana; (iv) plasmodesmata are observed between the stalk cell and the bladder cell, and between the epidermal cell and the stalk cell, and ectodesmata-like structures are observed on the bladder cell. Under high salinity conditions, (v) there is a clear tendency to accumulate greater amounts of K+ with respect to Na+ in the bladder cell; (vi) stalk cells accumulate similar amounts of K+ and Na+; (vii) Na+ accumulates mainly in the medullary parenchyma of the stem. These results add knowledge about the structure, content, and role of EBCc under salt stress, and surprisingly present the parenchyma of the stem as the main area of Na+ accumulation.